Высокое и низкое. История двух калош Вл. Соллогуба (The Sublime and the Base. The history of two galoshes by Vladimir Sollogub) - Egeberg, Erik (Poljarnyj vestnik, 2009)
This paper presents and discusses The history of two galoshes (1839) by count Vladimir Sollogub (1813-1882), a short-story with a pianist and composer of genius as its hero. The focus is on composition, authorial voice, use of clichés and features characteristic of Romantic literature.